2005
DOI: 10.1002/ddr.20041
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward re-engineering non-ribosomal peptide synthetase proteins: a potential new source of pharmacological agents

Abstract: Many important pharmaceutical agents, including vancomycin, bleomycin, cyclosporin, and several antibiotics, are produced by non-ribosomal peptide synthetase (NRPS) enzymes in microorganisms. The NRPS pathway produces an extensive library of products using multienzyme complexes acting in an assembly-line fashion. Engineering an NRPS system to produce an even greater variety of products, some of which may also have beneficial therapeutic value, would be an enormous advantage. Several approaches have been succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The primary substrate-specifying role of the A domain has made this domain a key target for NRPS recombination experiments. However, efforts to generate novel peptide products by modifying A domain substrate specificity, or by substituting in a non-synonymous A domain (that is, one which specifies an alternative monomer to the A domain it is replacing) have generally been unsuccessful [ 7 , 8 ]. Numerous in vitro e.g., [ 9 , 10 ] and in vivo [ 11 , 12 ] studies have demonstrated that the C domain typically “proof-reads” the downstream acceptor substrate (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The primary substrate-specifying role of the A domain has made this domain a key target for NRPS recombination experiments. However, efforts to generate novel peptide products by modifying A domain substrate specificity, or by substituting in a non-synonymous A domain (that is, one which specifies an alternative monomer to the A domain it is replacing) have generally been unsuccessful [ 7 , 8 ]. Numerous in vitro e.g., [ 9 , 10 ] and in vivo [ 11 , 12 ] studies have demonstrated that the C domain typically “proof-reads” the downstream acceptor substrate (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Non-ribosomal peptides (NRPs) are structurally complex natural products and potentially important antiinfective agents generated by non-ribosomal peptide synthetases (NRPSs), a family of large and modular multi-enzymes (Stevens et al 2005). In general, each module of NRPSs is composed of three core domains, condensation (C), adenylation (A), and peptidyl carrier protein (PCP) and the A-domain recruits a specific amino acid substrate to be incorporated into NRP structures (Marahiel et al 1997;Schwarzer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to generate novel peptide products in vivo by NRPS manipulation have involved either (i) replacement of the A domain by one that activates an alternative substrate, (ii) alteration of the substrate binding pocket of the A domain, or (iii) substitutions that treat C-A domains as inseparable pairs (8). However, in nearly all cases, these manipulations have resulted in little to no product being made.…”
mentioning
confidence: 99%